Determinants of Financial Distress Using Enterprise Risk Management as an Intervening Variable - Elfriandi Elfriandi; Sudjono Sudjono (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The purpose of this study is to determine the effect of leverage, liquidity, and cash flow operations on financial distress, with enterprise risk management as an intervening variable. For the period 2017-2021, this study was conducted at building construction service companies listed on the Indonesian stock exchange. Metodology/approach -The sampling technique used in this study is purposive sampling. The sample in this study are 17 companies of construction services companies listed on the Indonesian stock exchange during 2017 to 2021. The data analysis method is panel data regression analysis which is processed using the EViews program tool 12.0. .Findings - The results of this study indicate that leverage and liquidity have no effect on enterprise risk management, while cashflow operation has an effect on enterprise risk management. Furthermore, leverage, liquidity, enterprise risk management have no effect on financial distress, while cash flow operation has an effect on financial distress. On the intervening variable, enterprise risk management is unable to mediate the effect of leverage, liquidity, cash flow operations on financial distress. However, simultaneously as the result of F-test shows that leverage, liquidity and cashflow operation jointly have an effect to the enterprise risk management (ERM) and also leverage, liquidity, cashflow operation, and ERM have a joint effect on financial distress. Novelty/value – As the result of T statistic test and Sobel test found that cashflow operation affects ERM and financial distress. However, enterprise risk management as intervening is unable to mediate the effect of leverage, liquidity, cash flow operations on financial distress